The Role Of Interactive Methods In Modern Military Education - Abduraxmanov , Xalil Dilyaverovich (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article examines the role and significance of interactive teaching methods in the system of modern military education. The study uses literature analysis as its research method to explore how interactive teaching methods affect military training outcomes. The study results show that interactive teaching methods function as essential tools which help military students develop their tactical thinking and team management and decision-making abilities.